Rethinking industrial relations: mobilization, collectivism and long waves - Kelly, John (Abingdon, 1998)
"This original book is a wide-ranging, radical and highly innovative critique of the prevailing orthodoxies within industrial relations and human resource management. It covers: * central problems in industrial relations * the mobilization theory of collective action * the growth of non-union workplaces and the prospects and desirability of a new labour-management social partnership * an historical account of worker collectivism, organization and militancy and state or employer counter mobilization * a critique of postmodernism and accounts of the end of the labour movement. Containing a detailed examination of the evolution of industrial relations, it argues that the area is often under-theorized and influenced by the policy agenda of the state or employers, and will prove informative reading for students of industrial relations."